A Case Study on Engineering Failure Analysis of Link Chain - Tae-Gu Kim; Seong-Beom Lee; Hong-Chul Lee (Elsevier, 2010)
Objectives: The objective of this study was to investigate the effect of chain installation condition on stress distribution that could eventually cause disastrous failure from sudden deformation and geometric rupture. Methods: Fractographic method used for the failed chain indicates that over-stress was considered as the root cause of failure. 3D modeling and finite element analysis for the chain, used in a crane hook, were performed with a three-dimensional interactive application program, CATIA (Computer Aided Three dimensional Interactive Application), commercial finite element analysis and computational fluid dynamic software, ANSYS. Results: The results showed that the state of stress was changed depending on the initial position of the chain that was installed in the hook. Especially, the magnitude of the stress was strongly affected by the bending forces, which are 2.5 times greater (under the simulation condition currently investigated) than that from the plain tensile load. Also, it was noted that the change of load state is strongly related to the failure of parts. The chain can hold an ultimate load of about 8 tons with only the tensile load acting on it. Conclusion: The conclusions of this research clearly showed that a reduction of the loss from similar incidents can be achieved when an operator properly handles the installation of the chain.